Full-scale fatigue test and properties of low shrinkage LUHPC-steel composite bridge deck - Xiaoting Song; Baichuan Li; Jun Fu; Zheshi Wang; Qingjun Ding (Case Studies in Construction Materials)
A cost-effective low shrinkage steel-lightweight ultra-high performance concrete composite deck (SLCD) system, including orthotropic steel bridge decks (OSDs) and a low shrinkage lightweight ultra-high performance concrete (LUHPC) layer, is proposed to enhance the stiffness and fatigue performance of conventional OSD. Based on the example of China's Xintian Yangtze River Bridge, a three-dimensional finite element model was established to evaluate the nominal tensile stress of the LUHPC layer. A three-span continuous full-scale specimen with 6000 mm × 2000 mm was designed and tested under cyclic loading. The test results indicated that when the specimen stiffness across the central section decreased by 35.7 % after 100,000 cycles and thereafter remained almost unchanged even after one million cycles. After one million cycles, the strain values on the LUHPC surface at the mid-span section at 260 kN was about 275 με, which was far less than the ultimate flexural tensile strain of LUHPC (500 με), demonstrating the excellent crack resistance of the LUHPC layer. As the loading cycles neared 1.5 million, cracks within LUHPC developed from the adhesive side with the orthotropic plate to the bottom surface and finally reached up to 0.1 mm in width and 50 mm in length. Considering the effects of LUHPC’s aggregate density and low-shrinkage composite expansion agents, the existing S-N curves were modified to predict the fatigue cracking resistance of the SLCD. The results also showed that despite a marginal 2.56 % increase in weight and a 6.32 % rise in cost, the new pavement scheme experienced a significant reduction of 27.6 % in the peak tensile stress compared to the original pavement scheme, thereby improving the bridge deck’s fatigue performance. These findings are expected to provide a useful reference for the design and retrofit of the deck overlay of long-span bridges with OSD.